Pembangunan inklusif kelompok Difabel melalui program pemberdayaan CSR PT PJB UP Muara Tawar - Maygsi Aldian Suwandi; Widianto Dwi Ari Irawan; Rhima Rahmawati Fatimah (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
Inclusive Development become one of development mainstream that been promoted by many actors whether government, private sector and CSO. It emerges from a problem that there still many vulnerable groups excuded from development including difable. In order to support inclusive development, CSR PT PJB UP Muara Tawar implemented pemberdayaan Inklusi Tangguh dan Mandiri (Mentari) Bekasi program. The target of the program is Anggrek Karya Cacat Berkreasi group. The research used qualitative descriptive method. Concept used are inclusive development and CSR empowerment concept. In supporting inclusive development through difable empowerment, CSR PT PJB UP Muara Tawar raising awareness of potential difable, increasing capacity thoroughly in personal, intitutional and value system aspect and empowerment to ensure the sustainability and self reliance as a result of the program. Keywords : Inclusive Development, CSR Empowerment, Difable